2007
DOI: 10.1111/j.1365-4632.2007.03459.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin cancers at the National University Hospital of Cotonou from 1985 to 2004

Abstract: This study confirms the low incidence of skin cancer in the black population, the fact that basocellular carcinoma affects a relatively young population, and the predilection of melanoma for acral locations in black individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 5 publications
1
18
0
1
Order By: Relevance
“…Nevertheless, these latter studies included a relatively low number of annual histology specimens. Previous studies from African countries indicated SCC, followed by BCC, sarcomas and melanomas as the most frequent malignant skin tumours. In contrast, in our study KS with 35% of all malignant lesions was the most common malignant cutaneous tumour and overall also the most frequent histopathological diagnosis (8.5% of all diagnoses).…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, these latter studies included a relatively low number of annual histology specimens. Previous studies from African countries indicated SCC, followed by BCC, sarcomas and melanomas as the most frequent malignant skin tumours. In contrast, in our study KS with 35% of all malignant lesions was the most common malignant cutaneous tumour and overall also the most frequent histopathological diagnosis (8.5% of all diagnoses).…”
Section: Discussionmentioning
confidence: 98%
“…Melanoma is extremely rare among black populations in Africa and most cases of melanoma tend to be of the acral lentiginous subtype [58,59]. Immunosuppression as a result of HIV infection (Kaposi sarcoma), chronic ulceration, inflammation, albinism and UV exposure are identified risk factors for skin cancer in Africans.…”
Section: Ethnicity and Geographymentioning
confidence: 99%
“…A summary of the data from these studies is depicted in Table I. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Case 1 was a 69-year-old African American woman who presented with a 1-year history of a hyperpigmented scaly plaque on her left leg. The physical examination revealed a 2-cm black, hyperkeratotic plaque on the patient's left leg (Fig 1).…”
Section: Squamous Cell Carcinomas Of the Lower Limbs In African Amerimentioning
confidence: 99%